Correlation Between Corrected TIMI Frame Count with the Extent of Myocardial Fibrosis on ST-Elevation Myocardial Infarction Patients Undergoing Primary Percutaneous Coronary Intervention - Munandar, Reza Maulana; Herminingsih, Susi; Ardhianto, Pipin; Gharini, Putrika Prastuti Ratna; Sobirin, Mochamad Ali (Journal of Biomedicine and Translational Research, 2024)
Background: Microvascular injury after primary percutaneous coronary intervention (PPCI) reperfusion contributes to necrosis propagation. Corrected TIMI Frame Count (CTFC) is a surrogate marker of microvascular dysfunction and can stratify in-hospital mortality risk in patients with final TIMI flow 3. The extent of myocardial fibrosis after STEMI is associated with a higher incidence of major cardiovascular events. This study aimed to determine the relationship between CTFC in the infarct-related artery and myocardial fibrosis area based on cardiac magnetic resonance (CMR) in STEMI patients undergoing PPCI.Methods: This retrospective cohort study included 31 STEMI patients who had undergone PPCI and CMR examination between days 60 and 75 after STEMI as the sample. CTFC was measured in the infarct-related artery from post-PPCI angiogram recordings. Myocardial fibrosis area was measured from late gadolinium enhancement CMR (LGE-CMR) imaging results.Results: In this study, the mean age was 51.61±10.49 years, 90.3% were male, non-anterior infarction location was 58.1%, mean total ischemic time was 489.48±228.33 minutes, mean CTFC was 27.4±9.3 frames, and mean myocardial fibrosis was 18.33±7.87%. There was no significant correlation found between CTFC and myocardial fibrosis (p=0.530), however total ischemic time had a positive and significant correlation with myocardial fibrosis (p=0.025, r=0.403).Conclusion: CTFC in the infarct-related artery is not correlated with myocardial fibrosis area in STEMI patients undergoing PCI.